Surgeons’ Perspectives on Liability for the Use of Artificial Intelligence Technologies in the United States and European Union: Results From a Focus Group Study - Mindy Duffourc, JD, Dr Jur; Mathias Møllebæk, MA, PhD; Louise C. Druedahl, PhD, MScPharm; Timo Minssen, LLD, LLLic, Dipl Jur, LLM, MICL; Sara Gerke, Dipl-Jur Univ, MA (Annals of Surgery Open)
Objective:. To examine surgeons’ perspectives on liability for using artificial intelligence (AI)-driven technologies in surgery in the United States and the European Union. Background:. The introduction of AI-driven technologies in surgery can improve surgical performance and patient outcomes. However, liability risks might inhibit their implementation in the operating room. We report here the results of a focus group study that explored surgeons’ perspectives on liability for using AI-driven technologies in surgery in the United States and the European Union. Methods:. Participants were identified through a call for participation disseminated through personal and professional networks. Inclusion criteria were: (1) adults (at least 18 years of age); (2) surgeons based in either the United States or in one of the European Union’s Member States, with a preference for those specializing in gastrointestinal surgery to facilitate better discussions about the vignettes that involved a colorectal surgical procedure; (3) ability to comfortably read and communicate in English; (4) willingness to consent to participation, and (5) willingness to consent to keeping the focus group meeting content, participants, and discussions confidential. Results:. We conducted 6 focus groups via Zoom with a total of 18 participants (11 EU surgeons and 7 US surgeons). The following main themes emerged: (1) acknowledgment of the potential benefits of using AI-driven technology in surgery, (2) acceptance of surgeon responsibility, (3) recognition that AI may impact the standard of care, (4) skepticism about potential liability for AI manufacturers, and (5) the importance of patient information and consent. Conclusions:. Despite the potential future benefits of integrating AI into surgical practice, surgeons will benefit from (1) an increased understanding of how AI-driven technologies will deliver these benefits and (2) increased clarity surrounding how AI-driven technologies will be governed by both regulators and the surgical community. While our study focused on surgeons’ perspectives, it could also provide valuable insights for other healthcare providers using AI to treat patients.